Women and gender issues in British Paganism, 1945-1990 - Feraro, Shai (Palgrave historical studies in witchcraft and magic, 2020)
This book explores the ways in which changing views on gender and the place of women in society during the latter half of the twentieth century affected women's participation and standing within British Paganism. More specifically, it examines how British Wiccans and Wiccan-derived Pagans reacted to the rise of 'second-wave' feminism and the Women's Liberation Movement in the UK -- with a special emphasis on the reception of feminist theory hailing from the USA -- and to the emergence of feminist branches of Witchcraft and Goddess Spirituality during the 1970s and 1980s. The book draws on primary sources never before analyzed in an academic context and makes a valuable contribution to the growing body of knowledge on gender and religion during the twentieth century, as very little research has been conducted on the relations between the history of modern Paganism and that of second-wave feminism in the UK